"Are We All in This Together?": Brand Opportunism in COVID-19 Cause Related Marketing and the Moderating Role of Consumer Skepticism. Issue 6 (12th July 2021) - Yang, Jing; Mundel, Juan
Abstract: This study examined how the roles of perceived brand-social cause fit (i.e., functional fit and image fit) and consumer skepticism in influencing consumers' perception of brand opportunism and its subsequent outcomes during COVID-19 pandemic. A 2 (high vs. low fit) × 2 (industry: travel vs. grocery) between-participants online experiments ( n = 373) were conducted. Results showed that the lack of brand-social cause fit leads to less favorable consumer attitude due to their perception of the brand's opportunism. Specifically, with individuals high in skepticism, such perception of brand opportunism was greater, which in turn has a stronger negative influence on consumers' attitude toward the message and the brand. Theoretical contributions, managerial implications, limitations and future studies are also discussed.